Implementasi Kegiatan Layanan Bimbingan Dan Konseling Untuk Penguatan Karakter Disiplin Siswa Kelas IIIDi SD Muhammadiyah 21 Baluwarti Surakarta - Wulandari, Novi; , Dra. Risminawati, M.Pd (2017)
The purpose of this study is to describe the implementation of guidance and counseling service activities for strengthening the character of the discipline, as well as describe the constraints and solution implementation guidance and counselling activities in the grade III in the primary of Muhammadiyah Surakarta Baluwarti 21. This type of research is qualitative research diskriptif. Informants in this study is the head teacher of the school, class II and class III teachers. The validity of the data in this study using a triangulation of sources and methods. Method of data collection in this study i.e., interview, observation and documentation. Technical of data analysis is done interactively, include the reduction of the data, the presentation of the data and the withdrawal of the conclusion. Based on the results of this research can be concluded, namely (1) SD of Muhammadiyah Surakarta Baluwarti 21 already implemented three activities guidance and counseling services, (2) has implemented a service of guidance and counselling activities for strengthening the character of the discipline, by using the four components of the guidance and counselling services, and (3) constraints that occur in the implementation of guidance and counseling service activities for strengthening the character of the discipline of grade III i.e. students come to school late , do not enter school without permission, inappropriate behaviour in the classroom, and not dressed in uniform on the schedule, and the solutions that can be used is to find the root of the issues facing students with follow up.